Adaptive self-directed learning support by question generation in a semantic open learning space. (1st January 2013) - Jouault, Corentin; Seta, Kazuhisa
The objective of this research is to give learners content-dependent scaffolding during self-directed learning: the system is able to generate content-dependent support adapted to the learners. Learners use a system to perform a learning task in the domain of history. They have to build a concept map containing a chronology using the system. To be able to support, we combined multiple semantic information sources and Wikipedia, for the natural language information, to create a semantic open learning space. The system provides advice by generating questions based on the semantic information and enhancing document based on the Wikipedia corresponding to the semantic information. All the advices are provided on demand and are generated depending on the learner's concept map for adaptive support (question generation). The generated questions aim to lead the learners to new knowledge by deepening their understanding.